Preferred Formats of Arnis Sparring and Anyo Competition: Basis for an Enhanced Arnis Competition Framework - Anajao, Joel; Motita II , Paulo; Cuachin, Ronnel; Guanlao, Allan (International Journal of Sustainability and Advanced Integrated Research, 2026)
Sports Arnis is a distinct form of Filipino Martial Arts that sprang from a contemporary form of stick fighting, which was integrated into physical education and eventually evolved into a competitive form. This study examined the demographic profile of Arnis stakeholders and their preferences regarding sparring formats, weapons, scoring systems, judging systems, and Anyo competition structures across different age groups. An embedded mixed-method research design was employed, involving 362 respondents composed of players, coaches, and technical officials. Quantitative data were analyzed using frequency and percentage distributions, while qualitative responses were subjected to thematic analysis. Results showed a consistent preference for padded stick sparring, simple scoring systems, and the "first hit to score" concept across all age categories, particularly for young and grade school players. The judging system of one referee and three judges was overwhelmingly favored. In Anyo competitions, adults valued both traditional and non-traditional formats, while younger players showed a greater preference for non-traditional Anyo. Qualitative finding reveals key themes, including effective judging, improvement of protective gear, challenges related to camera or video support, the need for clearer scoring systems, and the preservation of authenticity in Traditional Anyo through standard appearance and reduced emphasis on acrobatics. The study concludes that Arnis stakeholders prioritize safety, fairness, simplicity, and cultural authenticity in competition. These findings provide empirical support for the development of standardized, age-group appropriate competition guidelines that balance modernization with the preservation of Arnis as a traditional Filipino martial art.